2017
DOI: 10.1016/j.mric.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Applications of PET/MR Imaging

Abstract: Synopsis PET/MR benefits neurological clinical care and research by providing spatially and temporally matched anatomic MR imaging, advanced MR physiologic imaging, and metabolic PET imaging. MR imaging sequences and PET tracers can be modified to target physiology specific to a neurological disease process, with applications in neuro-oncology, epilepsy, dementia, cerebrovascular disease, and psychiatric and neurological research. Simultaneous PET/MR provides efficient acquisition of multiple temporally matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 109 publications
(110 reference statements)
0
22
0
Order By: Relevance
“…In regard to emerging applications and new opportunities that complement the neuroimaging field in PET/MR, we wish to briefly highlight the following review papers. A review of the neurologic applications where the complementary natures of PET and MRI are beneficial in both research and clinics has been provided in Chen et al [14], Chen et al [196], Catana et al [197], Hope et al [198], Miller-Thomas and Benzinger [199]. The clinical applications where PET/MR might clinically excel are brain tumor imaging, epilepsy, stroke, and a number of neurodegenerative conditions, to name a few.…”
Section: Emerging Clinical and Research Applicationsmentioning
confidence: 99%
“…In regard to emerging applications and new opportunities that complement the neuroimaging field in PET/MR, we wish to briefly highlight the following review papers. A review of the neurologic applications where the complementary natures of PET and MRI are beneficial in both research and clinics has been provided in Chen et al [14], Chen et al [196], Catana et al [197], Hope et al [198], Miller-Thomas and Benzinger [199]. The clinical applications where PET/MR might clinically excel are brain tumor imaging, epilepsy, stroke, and a number of neurodegenerative conditions, to name a few.…”
Section: Emerging Clinical and Research Applicationsmentioning
confidence: 99%
“…Deng et al also observed that 18 F-FDG uptake was higher in the cerebral infarction area among drug treatment groups in a rat model of cerebral ischaemia reperfusion injury evaluated after 7 days [18]. Many previous studies have investigated perfusion and glucose metabolism using separate PET and MR procedures or integrated PET/MR in patients with cancer, Alzheimer's disease, epilepsy, and other disorders [21][22][23]. MR images and PET images can be obtained at different time points and fused for clinical and research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…PET/MRI has demonstrated great promise in areas where MRI is the predominant image modality, such as in neurological, cardiac, and soft tissue applications. [7][8][9] By combining the superior soft tissue contrast of MRI with the quantitative information of cellular activity and metabolism provided by PET, the diagnostic accuracy in glioma may likely improve. 10 Amino acid (AA) PET is recommended by current guidelines as a complement to CT or MRI in brain tumor diagnostics, resection, biopsy, treatment planning, and therapy response assessment.…”
mentioning
confidence: 99%